Sosialisai Produk Hukum Undang-Undang Nomor 35 Tahun 2009 tentang Narkotika dan P4GN (Pencegahan, Pemberantasan, Penyalahgunaan dan Peredaran Gelap Narkoba) Dewan Pengurus Cabang Pengajian Ahad Wage Perempuan Bangsa Kota Kediri - Aminah , Siti (Keris: Journal of Community Engagement, 2023)
Socialization of legal products in the form of Law No. 35 of 2009 on narcotics and socialization of P4GN (Prevention, eradication, abuse and illicit drug trafficking). This activity is a form of community service as an effort to know and understand the consequences of punishment for drug addicts, abuse and illicit drug trafficking contained in Law No. 35 of 2009 on narcotics. In order to prevent the eradication, abuse and illicit circulation of drugs that can harm, endanger the joint life of society, nation, and state. It requires knowledge, understanding related to the dangers of drugs. The form of this activity is the socialization of legal products in the form of socialization of Law No. 35 of 2009 on narcotics and socialization of P4GN (Prevention, eradication, abuse and illicit drug trafficking). This form of service activity provides an understanding to the community, about narcotics, narcotics precursors, production, import, export, illicit circulation of narcotics and Narcotics precursors, import and export approval letters, transportation, pharmaceutical wholesalers, narcotics transito, narcotics addicts, narcotics dependence, abusers, medical rehabilitation, social rehabilitation, conspiracy, wiretapping, organized crime, corporations and ministers. Participants of the socialization were mothers from the National Women's Branch Board of Kediri City. The purpose of this community service is to convey and provide understanding to mothers regarding the law on narcotics. Ensure narcotics security for the needs of health services and/or the development of Science and Technology, prevent, protect and save the Indonesian nation from narcotics abuse, eradicate illicit trafficking of narcotics and narcotics precursors. So Ibu2 as the first and main madrasah able to prevent early on the dangers of drugs for his family and the community around him. So that the realization of families and communities that Shine is clean from drugs.